Molecular Docking Analysis of Herbal Medicines for the Treatment of Diabetes Mellitus - Sethi, Amna Amin; Haleem, Madiha; Shar, Nisar Ahmed (Current Traditional Medicine, 2025)
BackgroundDiabetes Mellitus is a global health concern affecting millions of individuals worldwide. It is characterized by hyperglycemia resulting from insufficient insulin production or insulin resistance. Its high prevalence, especially in developing countries, such as Pakistan, demands effective and economically viable treatments.ObjectivesThe objective of this study was to identify herbal remedies for effectively targeting gluconeogenic enzymes in the treatment of diabetes mellitus. It aimed to explore herbal remedies for providing cost-effective alternatives with lesser side effects for the treatment of diabetes by targeting gluconeogenic enzymes.MethodsThe proteins of the already-known diabetic herb Momordica Charantia (Bitter melon) were initially investigated through molecular docking. Then, the proteins similar to the best-docked protein of Momordica Charactia were identified, and their molecular docking analysis was performed.ResultsThe results showed three plants having similar proteins to the Momrodica Charantia best-docked protein, namely Luffa Aegyptiaca (sponge gourd), Cucumis Sativus (cucumber), and Cucurbita Maxima (Pumpkin). The molecular docking analysis of these proteins revealed Cucumis Sativus (Cucumber) as a potential herbal candidate for the treatment of diabetes mellitus.ConclusionThe results of this study highlight the potential of Cucumis Sativus (Cucumber) for treating diabetes mellitus by targeting gluconeogenic enzymes. However, further research is necessary regarding the therapeutic potential of cucumber.
Keywords: herbal remedies